The decision of becoming a mother: Why some girls in foster group homes become adolescent mothers and others don’t? - Nair Elizabeth Zárate Alva; Josefina Sala-Roca; Laura Arnau-Sabatés (Interacciones)
The aim of this research is to analyze which factors can explain why some girls in foster group homes become adolescent mothers and others do not, exploring the contraception use, life and motherhood expectations and their family models. The study also analyzes how teen mothers in foster group homes experience motherhood and analyze the experience of becoming mothers in their lives while in care. A total of 36 girls from foster group homes (18 mothers and 18 non-mother girls) were interviewed. The results show that the need to fill their emotional emptiness, their lack of professional life expectations, their unrealistic expectations about parenthood and the role of their partner, and the undervalue of the conditions necessary to raise their children are the main factors involved. Most of the girls in the mother group were teen mothers who were sent to foster homes because of their premature motherhood. This shows that the educative work done by caseworkers can help girls to be more conscious about getting the suitable conditions before becoming mothers. The role of foster parents, social educators, social workers and mentoring programs with the purpose to empower mothers to prevent children neglect is discussed.